PROGRAM KKN: ULAR TANGGA UNTUK LITERASI DASAR MTS BENTENG HURABA - Fitri Agustina Lubis; Putoro Dongoran; Aslamiyah Rambe; Khoiriah Hasanah Nasution Khoiriah Hasanah Nasution; Ade Ningsih Satriono; Nurhayati Nurhayati (Linguistik : Jurnal Bahasa dan Sastra, 2026)
This study tested the effectiveness of a snakes and ladders game-based learning medium in improving student learning outcomes at Tsanawiyah Benteng Huraba. The background was limited learning facilities and infrastructure, which required teachers to be creative in improving teaching quality. The method used was a combination of meta-analysis and a quasi-experimental design. The snakes and ladders game was chosen as a medium to reduce boredom and increase student engagement. The results showed significant improvement. Before the intervention, only 55% of students achieved scores above the Minimum Mastery Criteria (KMA). After implementing this medium, all students (100%) successfully surpassed the KMA, representing a 45% increase in learning outcomes. These findings confirm that the use of game-based learning media facilitates material understanding, increases learning motivation, and ultimately optimizes student academic achievement. This study concludes that the snakes and ladders game is effective as an innovative alternative to addressing limited resources and improving the quality of classroom learning.